Government Financial Incentive and Firm Performance: Evidence from Turkey - Hussen, Mohamed Seid (International Journal of Economics, Management and Accounting, 2022)
Although government incentives to firms are common worldwide, empirical evidence of their impact on firm performance is rare. Against this backdrop, this study examines the causal impact of government financial incentives on firms labor productivity and export performance. We used a sample of Turkish firms obtained from the World Bank Enterprise Survey (WBES). The data were analyzed using Stata software, version 16. The empirical analysis employed the Propensity Score Matching (PSM) approach that controls for counterfactual outcomes. The study’s findings indicate that firms receiving government financial incentives are 33% more productive and export five times more than firms that do not. Therefore, it is essential to continue supporting firms to foster their performance, but future incentives should be given more to small and younger firms.